2022
DOI: 10.1039/d2cy01636b
|View full text |Cite
|
Sign up to set email alerts
|

Water-induced gaseous formaldehyde decomposition using ruthenium organic crystalline particles

Abstract: Formaldehyde is a hydrogen-containing chemical, it could react with water, making formaldehyde-water emerge as an attractive hydrogen storage system. However, formaldehyde also causes carcinogenic airborne pollutants released from paint, coating...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Additionally, X-ray diffraction (XRD) also confirmed that Ru-TMPD has a highly ordered crystalline structure. The XRD patterns show obvious peaks at 7.2°, 10.1°, 11.7°, 14.3°, 16.7°, 22.7°, and 28.1° . Other Ru-MOFs exhibited in Scheme have similar XRD peaks at 10.1° (Figures S17–S22).…”
Section: Results and Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Additionally, X-ray diffraction (XRD) also confirmed that Ru-TMPD has a highly ordered crystalline structure. The XRD patterns show obvious peaks at 7.2°, 10.1°, 11.7°, 14.3°, 16.7°, 22.7°, and 28.1° . Other Ru-MOFs exhibited in Scheme have similar XRD peaks at 10.1° (Figures S17–S22).…”
Section: Results and Discussionmentioning
confidence: 88%
“…The XRD patterns show obvious peaks at 7.2°, 10.1°, 11.7°, 14.3°, 16.7°, 22.7°, and 28.1°. 33 Other Ru-MOFs exhibited in Scheme 2 have similar XRD peaks at 10.1°(Figures S17−S22 Ru-TMPD has a high catalytic activity for hydrogen production from acetaldehyde and water reforming. As exhibited in Figure 2a, the gas is produced continuously in a 6 M acetaldehyde solution at 60 °C after Ru-TMPD is added to the solution.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 3 more Smart Citations